Analisis Kelayakan Investasi Menggunakan Metode Discounted Cash Flow pada Tambang Timah PT. Timah Tbk site TK Gemuruh Kecamatan Muntok, Kabupaten Bangka Barat, Kepulauan Bangka Belitung - cahaya permai hutahayan; Yoszi M Anaperta (Journals Mining Engineering : Bina Tambang, 2021)
PT.Timah Tbk is a company that plans to mine lead with an IUP area of 235.692  HA in Bangka Belitung Province. In Muntok District, Bangka Barat Regency, The total reserves are 151 tons with a selling price of IDR 383.980.000 / ton which is estimated to have a mining life of 3 years. This study aims to analyze the feasibility of investing in lead mining in terms of technical, economic aspects, using the discounted cash flow (DCF) feasibility analysis method to see whether a mine with lead production is feasible or not. The results of this study, obtained cash out flow of IDR 20,482,692,562  and cash in flow of IDR 57,215,275,883. Based on the discounted cash flow (DCF) method, the NPV results were IDR 20,023,236,285  an IRR of 15%, PBP for 1 years and a PI of 4,8.